2023
DOI: 10.1002/adtp.202200260
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Binding Sites: Dualsteric Ligands for the Cannabinoid 2 Receptor (CB2R)

Abstract: The cannabinoid receptor subtype 2 (CB 2 R) is rapidly upregulated in neuroinflammatory processes and respective agonists have a high potential to combat several central nervous system disorders related to neuroinflammation and neurodegeneration. As a new strategy for ligand design, dualsteric binding is applied by chemically combining a positive allosteric modulator with an orthosteric ligand. The resulting two sets of potential dualsteric (or bitopic) ligands with different chain lengths of two to five methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 50 publications
2
15
0
2
Order By: Relevance
“…Linking at the meta position of the PAM benzyl was also investigated, as the optimal chain length for para connection (propylene linker) for the parent compound (B3) displayed comparable effects as meta connection with a butylene linker (B4m). 13 The two series of compounds were synthesized in convergent synthetic routes. Fragment 3 was synthesized in four steps according to literature procedures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linking at the meta position of the PAM benzyl was also investigated, as the optimal chain length for para connection (propylene linker) for the parent compound (B3) displayed comparable effects as meta connection with a butylene linker (B4m). 13 The two series of compounds were synthesized in convergent synthetic routes. Fragment 3 was synthesized in four steps according to literature procedures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This approach is especially promising for pathologies where the endogenous ligand is absent, like for acetylcholine deficiency in neurodegenerative diseases like AD . Two different approaches toward dualsteric heterobivalent ligands for CB 2 R have very recently been described by Gado et al and us. Gado et al discovered the first CB 2 R-selective PAM ( 1 , Figure ) and recently also obtained the first dualsteric ligand by linking their PAM to a structurally related orthosteric ligand. , Their dualsteric lead compound had anti-inflammatory effects in a human microglial cell inflammatory model and antinociceptive activity in vivo , observed in an experimental mouse model of neuropathic pain . In a recent work, we synthesized the dualsteric CB 2 R ligand B3 ( cf.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking is one of the most widely used approaches for the validation of dualsteric binding modes, probably due to its lower cost. 54,57,58,64,65,70–72,76–80,82–86,88,92–95,98–100,103,109,114,115,117,121–123,126,127,129,131,133,134,137,138,140,160,162,163,165–167,169,170,172,176,177,182,184,186,198,199,252 However, the setting of the docking box, which restricts the position of searching, should be taken great care of. If the box is narrowed to only the orthosteric and allosteric site or interaction between a certain residue and the modulator is forced, the validation could not be reliable because the dualsteric binding pose is used as prior.…”
Section: Methods To Validate Dualsteric Binding Modesmentioning
confidence: 99%
“…After a manual filtering, 133 research articles focusing on identifications of novel dualsteric modulators were found. Modulators targeting GPCR 50,53,56–137 or kinase 138–157 account for more than three quarters (Fig. 5).…”
Section: Targets For Dualsteric Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation